A novel metaheuristic method for solving constrained engineering optimization problems: Crow search algorithm. (June 2016) - Askarzadeh, Alireza
Highlights: A novel metaheuristic technique called crow search algorithm is proposed. Crow search algorithm is used to efficiently solve engineering design problems. Crow search algorithm works based on intelligent behaviors of crows. Crow search algorithm produces promising results compared to other algorithms. Abstract: This paper proposes a novel metaheuristic optimizer, named crow search algorithm (CSA), based on the intelligent behavior of crows. CSA is a population-based technique which works based on this idea that crows store their excess food in hiding places and retrieve it when the food is needed. CSA is applied to optimize six constrained engineering design problems which have different natures of objective functions, constraints and decision variables. The results obtained by CSA are compared with the results of various algorithms. Simulation results reveal that using CSA may lead to finding promising results compared to the other algorithms.